Energy dependent of oslds compared with tld in low and high energy photon beams - Yahya, Muhammad Hadzmi (Universiti Sains Malaysia, 2016)
The aim of this study to investigate energy dependent of OSLDs and TLD100 at low energy and high energy photon beam. All dosimeters were calibrated using Cs-137 at Secondary Standard Dosimetry Laboratory (SSDL) at Malaysia Nuclear Agency. TLD100 and OSLDs dosimeter were irradiated using Philips Optimum 80 General X-ray machine with different energy of 40 kVp, 81 kVp and 125 kVp respectively. For high energy measurement, both dosimeters were placed in water phantom at dmax then were irradiated under high energy photon using 6 MV and 10 MV which were generated by Siemens Primus Linear Accelerator (LINAC). Both dosimeters showed energy dependent. The OSL dosimeters give reliable of result percentage different compare to TLD100 at high energy. The percentage ifferent of OSLDs was less than 10% compared to TLD100 less than 19%. Chi square, X2 values OSLDs to theoretical in low photon energy were 83.16, 125.03 and 156.16 compare X2 values for TLD 100 were 10.89, 4.13 and 8.69. In high energy photon, X2 values for OSLDs 0.035 and 0.121 compare TLD100 were 1.989 and 3.845. For better result in dose measurement using TLD100 in high energy, we should calibrate it using high energy source such as Co-60.